О новой стратегии экономических реформ в Республике Афганистан - Совик (L.E. Sovik) Л.Е.; Саларзай (A. Salarzay) А. (Экономика и банки, 2017)
Проводимая в Афганистане стратегия рыночных преобразований привела к разрушению экономики, государственного устройства и вооруженным конфликтам. В статье предложена новая стратегия экономических реформ, направленная на модернизацию и укрепление редистрибутивных институциональных форм. Реформу в банковской сфере предложено построить на модели исламского банкинга в его современных модификациях. The strategy of market reforms, being held in Afghanistan, has led to the destruction of the economy, polity, and armed conflicts. The article proves the contradictory bеtween the Afghan society nature and the forced into application market institutions. It proposes a new strategy of economic reforms aimed at modernizing and strengthening the redistributive institutional forms. The new strategy of reforms in the banking sector is proposed to build on the model of Islamic banking in its modern versions.